Breves Reflexiones sobre el lavado de activos. Entrevista al doctor Sergio Mattos. - Hurtado Antonio, Krizia Estefanía; Terrazas Cosio, Bresia Rosalid; Queirolo Romero, Ana Paula (Derecho & Sociedad, 2012)
El artículo no presenta resumen.